Digital Code-Mixing and Language Creativity among Youth: A Linguistic and Educational Perspective on English Loanwords in Social Media - Marco Bianchi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2015)
The rapid expansion of digital communication has significantly reshaped language practices, particularly among young people in multilingual contexts. Social media platforms have become dynamic spaces where linguistic creativity, identity construction, and informal learning intersect, leading to increased code-mixing and the widespread use of English loanwords. This study explores the use of English lexical items in youth digital discourse from the perspectives of linguistics, arts, and education. Adopting a quantitative survey design, data were collected from 410 urban youth aged 16–24 through a structured questionnaire examining language attitudes, creative expression, and digital communication practices. Descriptive statistics and exploratory factor analysis were employed to identify patterns of usage and underlying attitudinal dimensions. The findings reveal that English loanwords are widely accepted and frequently used, primarily due to their association with modernity, stylistic flexibility, and global cultural affiliation. Three key dimensions emerged: Linguistic Prestige, Creative Expression, and Cultural Integration. From an artistic perspective, code-mixing serves as a medium for stylistic innovation and identity performance, enabling youth to experiment with hybrid language forms. From an educational standpoint, digital communication functions as an informal learning environment where exposure to multilingual practices enhances linguistic awareness and adaptability. Despite the widespread use of English loanwords, participants also expressed awareness of the importance of maintaining local languages as part of their cultural identity. The study highlights the role of digital spaces as sites of both linguistic transformation and creative expression, suggesting that educators should consider integrating digital language practices into language learning to better align with students’ communicative realities. Future research is recommended to incorporate discourse and corpus-based approaches to further examine authentic language use and its implications for language education and cultural studies.